Moderate Toxicity of Potential Boron-containing Therapeutic, Dipotassium-trioxohydroxytetrafl uorotriborate -K2(B3O3F4OH) in Rats and Mice (Brazilian Journal of Pharmaceutical Sciences, 2023)
Biological activity of boron-containing compounds (BCCs) has been well-known. Growing interest and numerous applications for BCCs have been reported. Boron and boron-containing acids show low acute toxicity in mammals but data on halogenated boroxine (HB) - dipotassium-trioxohydroxytetrafluorotriborate, K2(B3O3F4OH) acute toxicity have not been reported before. This compound, characterized as a potential therapeutic for skin changes, exhibits no observable genotoxicity in doses lower that 0.1 mg/ml in vitro and 55 mg/kg in vivo. It has also been confirmed as an antitumour agent both in vitro and in vivo as well as an inhibitor of enzymes involved in antioxidant mechanisms. The aim of this study was to assess the acute toxicity of HB and to determine the maximum tolerated dose as well as a dose free of any signs of toxicity in different test organisms. Acute toxicity of HB was tested in Sprague-Dawley and Wistar rats and BALB/c mice after single parenteral application of different doses. We determined doses free of any sign of toxicity and LD50 after single dose administration. LD50 of HB ranges from 63 to 75 mg/kg in different test models, meaning that HB shows moderate toxicity.